2019
DOI: 10.1186/s12931-019-1193-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of umeclidinium/vilanterol versus umeclidinium and salmeterol monotherapies in symptomatic patients with COPD not receiving inhaled corticosteroids: the EMAX randomised trial

Abstract: BackgroundProspective evidence is lacking regarding incremental benefits of long-acting dual- versus mono-bronchodilation in improving symptoms and preventing short-term disease worsening/treatment failure in low exacerbation risk patients with chronic obstructive pulmonary disease (COPD) not receiving inhaled corticosteroids.MethodsThe 24-week, double-blind, double-dummy, parallel-group Early MAXimisation of bronchodilation for improving COPD stability (EMAX) trial randomised patients at low exacerbation risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(146 citation statements)
references
References 30 publications
8
131
1
6
Order By: Relevance
“…In a subset of patients (n = 4005), the relative risk of achieving a clinically important improvement in trough FEV 1 of ≥100 mL with LAMA/LABA versus LAMA was 1.33 (95% CI: 1.20, 1.46) and the number needed to treat to achieve this treatment benefit (NNTB) was 8 (95% CI: 6, 9; n = 1996). In addition, in the 24week randomized controlled EMAX study in symptomatic patients at low risk of exacerbations who were not receiving ICS, change from baseline in trough FEV 1 at Week 24 was 66 mL greater among patients treated with umeclidinium/ vilanterol compared with those treated with umeclidinium (95% CI: 43, 89; P < 0.001) [10].…”
Section: Lung Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a subset of patients (n = 4005), the relative risk of achieving a clinically important improvement in trough FEV 1 of ≥100 mL with LAMA/LABA versus LAMA was 1.33 (95% CI: 1.20, 1.46) and the number needed to treat to achieve this treatment benefit (NNTB) was 8 (95% CI: 6, 9; n = 1996). In addition, in the 24week randomized controlled EMAX study in symptomatic patients at low risk of exacerbations who were not receiving ICS, change from baseline in trough FEV 1 at Week 24 was 66 mL greater among patients treated with umeclidinium/ vilanterol compared with those treated with umeclidinium (95% CI: 43, 89; P < 0.001) [10].…”
Section: Lung Functionmentioning
confidence: 97%
“…A pooled analysis of data from 23 randomized trials including 23,213 patients with COPD also found statistically significant improvements in SGRQ and TDI scores and a reduction in rescue medication use with LAMA/ LABA versus LAMA monotherapy [14]. In patients treated with umeclidinium/vilanterol in the EMAX study, consistently greater improvements in TDI score at Week 24 (0.37; 95% CI: 0.06, 0.68; P = 0.018) and significantly higher odds of responding (odds ratio: 1.43; 95% CI: 1.17, 1.75; P < 0.001) were observed versus patients receiving umeclidinium monotherapy [10].…”
Section: Symptoms and Quality Of Lifementioning
confidence: 99%
“…Similarly, a post hoc analysis of three 24-week randomized studies comparing UMEC/VI and TIO in symptomatic patients with low exacerbation risk, UMEC/VI significantly reduced the risk of short-term CID versus TIO by 38 and 34% in the intent-to-treat and maintenance-treatment-naïve populations, respectively [41]. In contrast to the analyses described above, which were performed post hoc, the recent EMAX study, performed in a symptomatic low exacerbation risk population who were not receiving ICS, prospectively evaluated CID risk and showed that UMEC/VI significantly reduced the risk of a first CID compared with UMEC (17%) and salmeterol (38%) [46].…”
Section: The Composite Cid In Different Patient Populationsmentioning
confidence: 99%
“…The benefits of dual LAMA/LABA therapy versus monotherapies have been shown in other recent clinical trials. The EMAX trial, for example, showed that the proportion of responders was greater for all symptom outcomes in patients randomized to receive dual bronchodilator therapy (umeclidinium/vilanterol) versus those treated with umeclidinium or salmeterol [13]. Additionally, in these symptomatic, low exacerbation-risk patients with COPD, dual bronchodilation provided early and sustained improvements in lung function and symptoms, with reduced probability of short-term COPD worsening, compared with monotherapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…The EMAX trial, for example, showed that the proportion of responders was greater for all symptom outcomes in patients randomized to receive dual bronchodilator therapy (umeclidinium/vilanterol) versus those treated with umeclidinium or salmeterol [13]. Additionally, in these symptomatic, low exacerbation-risk patients with COPD, dual bronchodilation provided early and sustained improvements in lung function and symptoms, with reduced probability of short-term COPD worsening, compared with monotherapy [13]. In a pooled analysis of 23 clinical studies, where 53.6% of patients were receiving ICS alongside their current therapies, it was reported that combining LAMA/LABA therapies provided numerically better treatment outcomes than LAMA or LABA monotherapies for FEV 1 , SGRQ, and TDI [14].…”
Section: Discussionmentioning
confidence: 99%